2008
DOI: 10.1007/s15010-008-7328-4
|View full text |Cite
|
Sign up to set email alerts
|

Community-Acquired Pseudomonas aeruginosa Urinary Tract Infections in Children Hospitalized in a Tertiary Center: Relative Frequency, Risk Factors, Antimicrobial Resistance and Treatment

Abstract: Pseudomonas UTI seems to increase in CA, hospital-treated children and is often treated inappropriately according to current treatment protocols. Awareness of this trend and knowledge of the defined risk factors of Pseudomonas UTI might improve the empiric antibiotic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 22 publications
2
28
0
Order By: Relevance
“…Different drugs have different drug resistance rates. Gad et al [22] and Marcus et al [23] reported a higher drug resistance rate with levofloxacin than the studies reported by Bitsori et al [15], Narten et al [24] and Shigemura et al [25], but a lower rate with amikacin than the studies reported by Narten et al [24] and Shigemura et al [25]. This result may be due to the differing antibacterial use guidelines in different hospitals.…”
Section: Discussionmentioning
confidence: 97%
“…Different drugs have different drug resistance rates. Gad et al [22] and Marcus et al [23] reported a higher drug resistance rate with levofloxacin than the studies reported by Bitsori et al [15], Narten et al [24] and Shigemura et al [25], but a lower rate with amikacin than the studies reported by Narten et al [24] and Shigemura et al [25]. This result may be due to the differing antibacterial use guidelines in different hospitals.…”
Section: Discussionmentioning
confidence: 97%
“…Changes in the characteristics and causative pathogens of UTIs in hospital-treated children are continuously being reported [2,4,[6][7][8]. Concomitantly, changes in the antibiotic susceptibility patterns of pediatric uropathogens [2,3,[9][10][11] affect the empiric treatment of resultant infections.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning urine cultures more specifically, some studies demonstrated that inadequate initial antimicrobial treatment could lead to longer duration of hospitalization. However, this association was mainly noted in non‐ E. coli urinary tract infections, in children with urinary or renal abnormalities, or in children who had received antimicrobial therapy in the previous month [18,19]. Similarly, a study conducted in a tertiary‐care hospital and a community hospital demonstrated a significant association between inadequate initial antimicrobial treatment and mortality in cases of infections due to extended‐spectrum β‐lactamase‐producing Enterobacteriaceae .…”
Section: Discussionmentioning
confidence: 99%